2013
DOI: 10.3389/fnhum.2013.00826
|View full text |Cite
|
Sign up to set email alerts
|

Hyperactivation of the habenula as a link between depression and sleep disturbance

Abstract: Depression occurs frequently with sleep disturbance such as insomnia. Sleep in depression is associated with disinhibition of the rapid eye movement (REM) sleep. Despite the coincidence of the depression and sleep disturbance, neural substrate for depressive behaviors and sleep regulation remains unknown. Habenula is an epithalamic structure regulating the activities of monoaminergic neurons in the brain stem. Since the imaging studies showed blood flow increase in the habenula of depressive patients, hyperact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
49
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(51 citation statements)
references
References 69 publications
1
49
0
1
Order By: Relevance
“…These findings suggest that activation of the LHb would induce an increase in REM sleep. This idea is consistent with the hypothesis that the LHb is hyperactive in patients with depression, who show reduced latencies to initiate REM sleep and increased REM sleep amounts [85]. However, one study reported that electrical stimulation of the LHb decreased REM sleep in cats [86].…”
Section: Sleep and Circadian Rhythmsmentioning
confidence: 63%
“…These findings suggest that activation of the LHb would induce an increase in REM sleep. This idea is consistent with the hypothesis that the LHb is hyperactive in patients with depression, who show reduced latencies to initiate REM sleep and increased REM sleep amounts [85]. However, one study reported that electrical stimulation of the LHb decreased REM sleep in cats [86].…”
Section: Sleep and Circadian Rhythmsmentioning
confidence: 63%
“…Much data indicates that the LHb may be a key brain region linked to depression since it negatively regulates the monoamine systems in the brain (Wang and Aghajanian, 1977;Christoph et al, 1986;Sartorius and Henn, 2007;Aizawa et al, 2013;Lecca et al, 2014). Indeed, previous studies have shown that increased LHb activity decreases the activity of DA neurons in the VTA (Christoph et al, 1986;Ji and Shepard, 2007) and 5-HT neurons in the raphe nuclei (Wang and Aghajanian, 1977;Stern et al, 1979).…”
Section: Depressive-like Behaviors Involve Increased Firing Activity mentioning
confidence: 96%
“…There is growing evidence that dysfunction of the LHb plays an important role in the pathophysiology of depression (Sartorius and Henn, 2007;Ranft et al, 2010;Aizawa et al, 2013;Lecca et al, 2014). Previous studies have found hyperactivity of the LHb during depressed states (Caldecott-Hazard et al, 1988;Morris et al, 1999;Shumake et al, 2003;Roiser et al, 2009;Li et al, 2011Li et al, , 2013, whereas reduction of LHb activity by electrolytic lesions (Amat et al, 2001;Yang et al, 2008), deep brain stimulation (DBS) (Sartorius et al, 2010;Li et al, 2011Li et al, , 2013 and pharmacological inhibition using the GABA A receptor agonist muscimol (Winter et al, 2011) have shown antidepressant effects in depressed patients and rat models of depression.…”
Section: Introductionmentioning
confidence: 97%
“…This issue appears relevant, regarding the modulatory role of the LHb upon dopaminergic and serotonergic transmissions (Bernard and Veh, 2012;Ji and Shepard, 2007;Wang and Aghajanian, 1977), as well the cholinergic septo-hippocampal pathway (Nilsson et al, 1990), which are key systems involved in memory processes. It is also relevant because dysfunction of the LHb has been evidenced in disorders such as depression (Aizawa et al, 2013a;Sartorius and Henn, 2007), which encompasses alterations of hippocampal networks, as well as memory impairments (Trivedi and Greer, 2014;Belzung et al, 2015;Lecca et al, 2014). In rats, LHb electric stimulation prevented avoidance learning (Shumake et al, 2010).…”
Section: Introductionmentioning
confidence: 99%